2000
DOI: 10.1074/jbc.275.16.11993
|View full text |Cite
|
Sign up to set email alerts
|

Rho-A Is Critical for Osteoclast Podosome Organization, Motility, and Bone Resorption

Abstract: Rho plays a regulatory role in the formation of actin stress fibers and focal adhesions, and it is also involved in integrin-mediated signaling events. To study the role of Rho in ␣ v ␤ 3 /gelsolin-dependent signaling, the HIV-Tat peptide, hemagglutinin (HA)-tagged Rho Val-14 (constitutively active) and Rho Asn-19 (dominant negative) were transduced into avian osteoclasts. Protein transduction by HA-Tat was highly efficient, and 90 -100% of the cells were transduced with HA-tagged proteins. We demonstrate here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
230
1
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(240 citation statements)
references
References 66 publications
8
230
1
1
Order By: Relevance
“…By contrast, concentrations of NE10790 that inhibited resorption (0.5-1 mM) had little effect on F-actin organization at the mineral surface, with no significant reduction in the number of F-actin rings. This is consistent with the evidence that regulation of the osteoclast cytoskeleton, required for bone resorption, involves small GTPases prenylated by GGTase I, such as Rho and Rac (16,(27)(28)(29). NE10790 specifically inhibits Rab prenylation by Rab GGTase, demonstrating for the first time that Rab proteins are also required for osteoclastic bone resorption.…”
Section: Figsupporting
confidence: 74%
“…By contrast, concentrations of NE10790 that inhibited resorption (0.5-1 mM) had little effect on F-actin organization at the mineral surface, with no significant reduction in the number of F-actin rings. This is consistent with the evidence that regulation of the osteoclast cytoskeleton, required for bone resorption, involves small GTPases prenylated by GGTase I, such as Rho and Rac (16,(27)(28)(29). NE10790 specifically inhibits Rab prenylation by Rab GGTase, demonstrating for the first time that Rab proteins are also required for osteoclastic bone resorption.…”
Section: Figsupporting
confidence: 74%
“…In the former case it was membrane ruffles, whereas in the latter, it was in podosome rosettes, the major actin structures in Src-transformed fibroblasts. Podosome formation is known to be Rho GTPase-dependent (Chellaiah et al, 2000;Chellaiah, 2005;Osiak et al, 2005), and we found that RhoGDI was closely associated with RhoA in the rosettes ( Figure 6C). RhoGDI Y156E -expressing cells exhibited increased cell spreading, membrane ruffling, and motility compared with the suppression of these responses by wild-type RhoGDI or RhoGDI Y156F .…”
Section: Discussionmentioning
confidence: 64%
“…However, miR‐31a‐5p reduction in the supernatant not only led to decreased osteoclastogenesis and bone resorption but also elevated expression of RhoA. Although studies have demonstrated that RhoA activity, controlling cytoskeleton organization, is crucial for osteoclast maturation and bone resorption (Chellaiah et al., 2000), it has also been reported that inhibition of RhoA maintained the podosomal and sealing zone stability, which is possibly correlated with increased microtubule acetylation and stabilization in osteoclasts (Destaing et al., 2005; Granot‐Attas, Luxenburg, Finkelshtein, & Elson, 2009; Ory, Brazier, Pawlak, & Blangy, 2008; Wu et al., 2017). In our study, increased RhoA expression through miR‐31a‐5p inhibition reduced osteoclastogenesis, while decreased RhoA expression favored osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 91%